Maintien de l'ordre : étude des projets gouvernementaux 420-421-422-424 du 16 août 1962 - De Kock, Marc; Lallemand, Roger; Moureaux, Serge; Schellekens, Jacques; Calewaert, Willy (Bruxelles: Marc De Kock, 1962)
"Marc De Kock, Roger Lallemand, Serge Moureaux, Jacques Schellekens ; préface de Willy Calewaert Archief André De SmetBibliotheek François Vercammen"